Community-Based Treatment for Individuals Convicted of Sexual Offenses Using the Integrated Risk Assessment and Treatment System Model Versus Standard Correctional Programming - Abracen, Jeffrey (Criminal justice and behavior, 2023)
The present investigation examined a group of 90 clients receiving treatment for issues related to sexual offending in The Central District (Ontario) Sex Offender Treatment Program operated by Correctional Service Canada (CSC). Treatment was provided in line with the Integrated Risk Assessment and Treatment System (IRATS) Model developed by the authors. A group of 55 individuals who had not received sexual offense–specific treatment but who received standard correctional programming offered by paraprofessionals were used as a basis of comparison. Risk assessment data were available for all clients included in the analyses. Results indicated that there were no differences between groups on the RRASOR (an actuarial instrument designed to assess risk of sexual offense recidivism) with reference to sexual offender recidivism risk. With reference to sexual offense recidivism, only one of the treated clients recidivated sexually over 8.17 years of follow-up versus four of the 55 comparison group who were followed for a significantly shorter period of time (i.e., 6.9 years).